Physical Education and its contribution to the comprehensive development of motor skills/Educación Física y su contribución al desarrollo integral de la motricidad - Jayson Bernate (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
Early childhood education is the first link through which the child begins with classroom training. This work will show the systematic compilation and analysis of specialized academic sources on the importance of school Physical Education and its contribution to the comprehensive development of motor skills in children. The contribution to learning through exploration, the game, the ludic and physical education, provides a comprehensive education in the motor field to infants. The objective of this article was to carry out a bibliographic-systemic review in specialized databases such as; Scopus, Ebsco, Dialnet, Redalyc, among others, on the importance and relevance of motor skills in the child population, visualizing the determining factors for the adequate development of the child, through the teaching and pedagogy of Physical Education and its different areas. The methodology developed was qualitative and its design is a bibliographic-systemic review, considering inclusion and exclusion criteria through categorical and heuristic matrices for the respective analysis of the information. The results illustrate that the training of school Physical Education is decisive and influential in the processes of motor and cognitive development of children, positively influencing these processes. As the main conclusion of the study, it can be inferred that the pedagogical approach of Physical Education encompasses a number of methods and tools, not only offering the possibility of promoting healthy lifestyle habits, but also optimizing motor development processes at school age.